1998
DOI: 10.1099/00221287-144-9-2449
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-starvation-induced chlorosis in Synechococcus PCC 7942: adaptation to long-term survival

Abstract: When deprived of essential nutrients, the non-diazotrophic cyanobacterium Synechococcus sp. strain PCC 7942 undergoes a proteolytic degradation of the phycobiliproteins, its major light-harvesting pigments. This process is known as chlorosis. This paper presents evidence that the degradation of phycobiliproteins is part of an acclimation process in which growing cells differentiate into non-pigmented cells able to endure long periods of starvation. The time course of degradation processes differs for various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 37 publications
3
113
0
1
Order By: Relevance
“…When ammonium was used as a nitrogen source, the nitrate salt from BG11 was replaced by 5 mM NH 4 Cl and the medium was buffered to pH 8.0 with 5 mM HEPES. Illumination was provided with standard fluorescent lamps at a photosynthetic photon flux density of 50 to 60 mol of photons m Ϫ2 s Ϫ1 , which resulted in generation times of 15 to 16 h. Nitrogen or sulfur step-down was initiated by filtration on polyvinylidene difluoride membranes and resuspension of the cells in medium deprived of a combined-nitrogen or sulfur source, as described previously (10). Cultures of MP2 and MNtcA were maintained in the presence of 25 g of kanamycin/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When ammonium was used as a nitrogen source, the nitrate salt from BG11 was replaced by 5 mM NH 4 Cl and the medium was buffered to pH 8.0 with 5 mM HEPES. Illumination was provided with standard fluorescent lamps at a photosynthetic photon flux density of 50 to 60 mol of photons m Ϫ2 s Ϫ1 , which resulted in generation times of 15 to 16 h. Nitrogen or sulfur step-down was initiated by filtration on polyvinylidene difluoride membranes and resuspension of the cells in medium deprived of a combined-nitrogen or sulfur source, as described previously (10). Cultures of MP2 and MNtcA were maintained in the presence of 25 g of kanamycin/ml.…”
Section: Methodsmentioning
confidence: 99%
“…strain PCC 7942) (13) and S. elongatus PCC 7942 mutants MP2, lacking the P II signaling protein (glnB::aphII) (6), and MNtcA, lacking the NtcA protein (ntcA::aphII) (31). Cells were grown in liquid BG11 medium (28) at 30°C as described previously (10). When ammonium was used as a nitrogen source, the nitrate salt from BG11 was replaced by 5 mM NH 4 Cl and the medium was buffered to pH 8.0 with 5 mM HEPES.…”
Section: Methodsmentioning
confidence: 99%
“…Although the specific growth rate for A. flos-aquae was negative between Day 0 and Day 7 in all treatments, it is positive between Day 7 and Day 14. This indicates a longer acclimatization time for A. flos-aquae and it would have been interesting to continue the experiment (compare e.g., [59,78], Wulff et al, unpublished). D. lemmermannii had negative specific growth rate in all treatments throughout the experiment.…”
Section: Biovolume and Growthmentioning
confidence: 99%
“…Recently, it was shown that the complete depigmentation of cells of the obligate photoautotroph Synechococcus strain PCC 7942 is not a consequence of loss of cell viability but a specific acclimation process which enables the cells to survive for prolonged periods of nitrogen starvation (12). This acclimation process proceeds in three phases.…”
mentioning
confidence: 99%
“…The rapid trimming and degradation of the phycobilisomes (phase 1) (2, 12) is followed by a gradual loss of chlorophyll a (Chl a) and intracellular proteins (phase 2). Finally, the cells lose all visible pigmentation and enter a form of dormancy (phase 3), from which they are able to reinitiate growth within 3 to 4 days following the addition of a combined nitrogen source (12).…”
mentioning
confidence: 99%